Media design made from recycled materials for muhammadiyah 2 Langsa students - Afifah, Reihan Dinda; Sari, Rita; Anggreni, Fenny (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2022)
The lack of use of learning media makes it difficult for students to understand the material. As a result, student test results have not optimally met the KKM score. Therefore, it is necessary to design a learning media so that the results achieved by students become better. The purpose of this study was to describe the stages of developing a magic box from recycled materials with the theme of weather at SD Muhammadiyah 2 Langsa, to determine the feasibility of developing magic box media, teacher and student responses, and to determine the learning outcomes obtained by students after using magic box media. This research method is (R&D) with the ADDIE development model which consists of 5 stages of development, including the stages of analysis, design, development, implementation, and evaluation. The results of this study are material expert validation of 80%